Gambaran Pengetahuan Dan Metode Menyikat Gigi Pada Anggota Karang Taruna Dusun Bungas Sumberagung - Ika Sulistyani; Quroti A’yun; Sutrisno Sutrisno (Poltekkes Kemenkes Yogyakarta, 2017)
Knowledge was the result of everybody’s knowledge who did sense to a certain object. Brushing teeth method was the common way that was supposed to clean “deposite lunak” at this surface of the teeth and gum that was preventive action on testing of cleanliness and health of oral cavity which is optimum. This result aimed to know the description of knowledge of brushing teeth in karang taruna members in Bungas Sumberagung Jetis Bantul. The type of this result was descriptive the sample was taken in this result were 40 karang taruna mamber’s. The aspect that was studied in this result was the knowledge of brushing teeth. The data presentation was analyzed of the front cross tabulation. The result of this result depended on gender there were 20 male teenagers and 20 female teenagers. Meanwhile, according to age, there was a most teenager by the age of 16-20 years, with 26 participants. The best criteria of knowledge brushing teeth with 27 participants (67,%%), meanwhile combination method were the most 18 participants (45%). Based on cross tabulation between knowledge and brushing teeth method so the description of knowledge and brushing teeth method in Karang Taruna members was the best criteria knowledge and brushing teeth combination method with 17 participants (42,5%)and the bad of knowledge of brushing teeth vertical method was 1 participant (2,5%).